The experience of application of space images for creation of the land use map of irrigated lands and laylands of svetloyarsk irrigation system - I. N. Gorokhova; E. I. Pankova; E. A. Shishkonakova (Бюллетень Почвенного института им. В.В. Докучаева, 2017)
The experience of space images use for creation of land use map for the terriotory of the Svetloyar irrigation system and neighboring households is considered. The investigation territory is located in the north-west area on the right bank part of Kaspian lowland (Volgograd oblast). The land use map reflects the actual conditions of the object and contains the information about the fields under different crops and mixed-age laylands. In order to determine the mixed age layland, the field data were used, which allowed us to reveal the vegetation composition, which varies due to the age of layland. Space images also reflect this specificity. The creation of land use map is a necessary stage of soil-saline map creation. The complex analysis of data obtained on the basis of space images, recognaissance operations and field works, meliorative cadasters, land use map allowed us to assess the actual conditions in the investigation region. We also revealed the following: at the present slightly more than 50% of irrigated lands are used, 86% of them are occupied by winter wheat, and the rest of the area is under the forage grasses. The other half of lands is presented by mixed age laylands. During the crop cultivation preirrigation and drop irrigation was used. As a result the ground water level decreased below the 5 m almost everywhere.